2021
DOI: 10.3389/fpls.2021.719987
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Host-Specific Competitiveness of the Symbiont Rhizobium leguminosarum Symbiovar viciae

Abstract: Legumes of the Fabeae tribe form nitrogen-fixing root nodules resulting from symbiotic interaction with the soil bacteria Rhizobium leguminosarum symbiovar viciae (Rlv). These bacteria are all potential symbionts of the Fabeae hosts but display variable partner choice when co-inoculated in mixture. Because partner choice and symbiotic nitrogen fixation mostly behave as genetically independent traits, the efficiency of symbiosis is often suboptimal when Fabeae legumes are exposed to natural Rlv populations pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 75 publications
(128 reference statements)
0
25
1
Order By: Relevance
“…Such compounds can directly or indirectly stimulate plant growth and may promote plant adaptation to various stresses ( Purwaningsih et al, 2021 ). Rhizobium is a natural PGPR in the rhizosphere used in farming to enhance legume crops’ growth through mutually beneficial relationships ( Allito et al, 2021 ; Boivin et al, 2021 ). This way, finding new biocontrol agents that are safe for the environment, control plant viruses, and fix nitrogen is a top priority for food security.…”
Section: Discussionmentioning
confidence: 99%
“…Such compounds can directly or indirectly stimulate plant growth and may promote plant adaptation to various stresses ( Purwaningsih et al, 2021 ). Rhizobium is a natural PGPR in the rhizosphere used in farming to enhance legume crops’ growth through mutually beneficial relationships ( Allito et al, 2021 ; Boivin et al, 2021 ). This way, finding new biocontrol agents that are safe for the environment, control plant viruses, and fix nitrogen is a top priority for food security.…”
Section: Discussionmentioning
confidence: 99%
“…While our results suggest that OE strains could be highly competitive, their frequency is relatively low in white clover nodule populations across Europe, while the gsC strains are often the most abundant (Kumar et al ., 2015; Cavassim et al ., 2020; Moeskjaer et al ., 2020). Relatively higher frequencies of gsE strains have however been observed in pea and faba bean nodules (Boivin et al ., 2020), which suggest that their abundance could also depend on the specific legume host. Overall, the observed link between rhizobial genotypes and phenotypes, could potentially be explained by local adaptation and niche specialization, enabling strains to coexist in sympatry within the competitive rhizosphere environment (Hunt et al ., 2008; Oakley et al ., 2010; Koeppel et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that natural rhizobium populations in the soil are often very diverse (Kumar et al, 2015) and strains previously categorized as R. leguminosarum form a species complex of at least 18 genospecies that are separated by average nucleotide values below 96% (Kumar et al, 2015;Cavassim et al, 2019;Young et al, 2021). Up to five of these genospecies have been documented to live in sympatry in rhizosphere (Kumar et al, 2015;Boivin et al, 2020;Cavassim et al, 2020), and they include host-specific symbiovars that nodulate clover (Rhizobium leguminosarum symbiovar trifolii; Rlt) and vetch (Rhizobium leguminosarum symbiovar viciae). Multiple factors including plant species and varieties (Miranda-S anchez et al, 2016;Vuong et al, 2017;Clúa et al, 2018), soil abiotic properties (Rice et al, 1977;Harrison et al, 1989;Xiong et al, 2017;Liu et al, 2019), agricultural management practices (Kiers et al, 2002;Shu et al, 2012;Weese et al, 2015), and microbial competition (Schwinghamer and Brockwell, 1978;Wilson et al, 1998;Hibbing et al, 2010) could drive and maintain rhizobial diversity, providing different ecological opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis based on a portion of the chromosomal gyrB gene demonstrated that these 20 strains clustered in two closely related clades of the R. leguminosarum species complex (Young et al, 2021; Figure 1A). The first clade includes the Rlv strains TOM, FRF1D12, Vaf10 and CCBAU83268 belonging to genospecies gsN (Boivin et al, 2020), and the second clade includes the Rlv strain SL16 belonging to the genospecies gsR (Boivin et al, 2020). Three strains (FWPou15, FWPou32 and FWPou38) randomly selected from the most predominant clade were further characterized.…”
Section: Resultsmentioning
confidence: 99%
“…viciae ( Rlv ) are associated with wheat roots. (A) Neighbour‐Joining tree based on a portion of the chromosomic gyrB gene from the 20 wheat‐isolated strains (indicated in blue), a set of Rlv strains representative of the diversity of the species complex (Boivin et al, 2021), and the strain A34. Ensifer meliloti was used as outgroup.…”
Section: Resultsmentioning
confidence: 99%